MOF for template-directed growth of well-oriented nanowire hybrid arrays on carbon nanotube fibers for wearable electronics integrated with triboelectric nanogenerators. (March 2018) - Zhao, Jingxin; Li, Huayang; Li, Chaowei; Zhang, Qichong; Sun, Juan; Wang, Xiaona; Guo, Jiabin; Xie, Liyan; Xie, Jixun; He, Bing; Zhou, Zhenyu; Lu, Conghua; et al.
Abstract: An integrated self-charging power system incorporating flexible fiber-shaped coaxial asymmetric supercapacitors (FASCs) with flexible triboelectric nanogenerators (FTENGs) has the potential to harvest and store energy simultaneously for achieving self-charged power pack. In this study, we develops a new strategy for fabricating a metal-organic framework (MOF) for the template-directed growth of hierarchically well-oriented nanowire arrays based on carbon nanotube fibers (CNTFs) for electrochemical supercapacitors. Uniform CNTFs@ZnCo2 O4 @Zn-Co-S hybrid arrays (HAs) derived from a zinc/cobalt-based zeolitic imidazolate framework (Zn/Co-ZIF) are first fabricated via a facile annealing and sulfuration process and a CNTFs@H-Co3 O4 @CoNC HA derived from a Co-based MOF is synthesized via oxidation and carbonization processes; the products act as positive and negative electrodes respectively in the assembled FASCs. The as-prepared CNTFs@ZnCo2 O4 @Zn-Co-S HAs and CNTFs@H-Co3 O4 @CoNC HAs are endowed with rich reaction sites, a facile ion diffusion path, and improved conductivity because of their unique hierarchical structure and good synergistic effect, which improves the electrochemical properties of the MOF derivatives. In addition, the assembled FASCs device exhibits a remarkable electrochemical performance with excellent rate capability. This study provides a strategy for the rational design of hierarchically structured, well-oriented MOFs and derivative arrays with high electrochemical performance and mechanical flexibility. Moreover, the flexible fiber-shaped MOF–derivative HA asymmetric supercapacitor is charged by a flexible triboelectric nanogenerator, demonstrating the promise of an self-charging power pack that has considerable potential for developing flexible multifunctional electronic devices. Graphical abstract: A self-charging power system is developed, which exhibits stable output of FTENGs and excellent electrochemical performance of FASCs.fx1 Highlights: We have designed and fabricated novel ZnCo2 O4 @ZnCo2 O4, ZnCo2 O4 @Zn-Co-S, and H-Co3 O4 @CoNC on flexible CNTFs. The assembled flexible FASC possesses excellent electrochemical performance. A self-charging power system are developed and are composed of FASCs and FTENGs.